2005
DOI: 10.1097/01.jcp.0000178415.22309.8f
|View full text |Cite
|
Sign up to set email alerts
|

Aripiprazole for the Treatment of Psychosis in Patients With Alzheimer's Disease

Abstract: This study compared the efficacy, safety, and tolerability of aripiprazole, a novel antipsychotic, with placebo in patients with psychosis associated with Alzheimer's Disease (AD). This 10-week, double-blind, multicenter study randomized 208 outpatients (mean age, 81.5 years) with AD-associated psychosis to aripiprazole (n = 106) or placebo (n = 102). The initial aripiprazole dose of 2 mg/d was titrated upwards (5, 10, or 15 mg/d) according to efficacy and tolerability. Evaluations included Neuropsychiatric In… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
117
1
2

Year Published

2005
2005
2019
2019

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 143 publications
(125 citation statements)
references
References 24 publications
5
117
1
2
Order By: Relevance
“…Shapiro et al (80) predicted on the basis of its 5-HT 2A /5-HT 2C profile that aripiprazole would have anorectic actions in humans. Aripiprazole is also being investigated in psychosis associated with Alzheimer's disease (24). A report from the multicenter, double-blind placebo-controlled trial involving 208 outpatients (mean age 81.5 years) indicated that aripiprazole may cause improvements in the Neuropsychiatric Inventory (NPI) Psychosis scale and in a subscale (delusions and hallucinations) of The Brief Psychiatric Rating Scale (BPRS).…”
Section: Other Disordersmentioning
confidence: 99%
“…Shapiro et al (80) predicted on the basis of its 5-HT 2A /5-HT 2C profile that aripiprazole would have anorectic actions in humans. Aripiprazole is also being investigated in psychosis associated with Alzheimer's disease (24). A report from the multicenter, double-blind placebo-controlled trial involving 208 outpatients (mean age 81.5 years) indicated that aripiprazole may cause improvements in the Neuropsychiatric Inventory (NPI) Psychosis scale and in a subscale (delusions and hallucinations) of The Brief Psychiatric Rating Scale (BPRS).…”
Section: Other Disordersmentioning
confidence: 99%
“…Th ree RCTs comparing aripiprazole with placebo in AD patients for treatment of agitation and psychosis demonstrated reasonable tolerability and benefi ts signifi cantly greater than placebo [85][86][87]. In a meta-analysis of these trials, the pooled estimate of eff ect sizes was small but statistically signifi cant and similar to benefi ts found with risperidone and olanzapine [88].…”
Section: Rationalementioning
confidence: 89%
“…Olanzapine also showed a two-fold increase in mortality in dementia patients, despite promising evidence from trials and case reports (Wathion, 2004). The newest anti-psychotic in the UK, Aripiprazole,has also been trailed with some success in patients with BPSD, but again has shown an increase in CVAE (De Deyn et al, 2003;Breder et al, 2004;Streim et al, 2004). The safety profile of other antipsychotic agents remains a topic of some uncertainty at the time of writing.…”
Section: Symptomatic Pharmacotherapymentioning
confidence: 96%